Optimal pricing and regulation of transport externalities: A welfare comparison of some policy alternatives - Bruno L. DeBorger; Didier Swysen (Fondazione Eni Enrico Mattei (FEEM), 1997)
The purpose of this paper is to present and apply a simple framework for studying optimal prices and regulations for passenger and freight transport, taking into account the heterogeneity of transport services, and capturing all major external costs, viz. congestion, air pollution, accident risks and road depreciation. Based on a straightforward theoretical structure a simulation model is developed in which the heterogeneity of transport services (various modes, periods, fuel types, etc...) is captured through the use of nested-CES utility and production functions. The authority chooses optimal taxes and decides which technologies have to be implemented from a social welfare viewpoint. In a first application of the model we consider both optimal pricing policies and the desirability of introducing improved engine technologies in cars. The results suggest that substantial welfare gains could be realised. Moreover, they clearly illustrate the importance of the set of instruments available to the government. For example, the absence of a toll or road pricing system that allows differentiation between peak and off-peak periods reduces the potential welfare gain of pricing policies by some 60%.
Keywords: 330